Pengaruh Modul Pembelajaran dan Kecerdsasan Intrapersonal terhadap Hasil Belajar kimia Siswa di SMPN 90 Jakarta - I Ketut Ulianta; Moch. Sukardjo; Priono Priono (JTP - Jurnal Teknologi Pendidikan, 2020)
This study aims to find out the impact of instructional media and intrapersonal intelligence on the learning outcome of Chemistry course of students of SMP Negeri 90 Jakarta. This study applies experimental method with Treatment by level 2x2 research design. For data collection purposes, this study uses multiple choice test to collect data of the students’ learning outcome and questionnaire to collect data of the students’ intrapersonal intelligence. The result of this study shows that : (1) learning outcome of Chemistry course of the students who were given internet-based instructional media is higher than those who were given module-based instructional media, (2) there is interactional influence between instructional media and intrapersonal intelligence on the learning outcome of Chemistry course of the students, (3) for students who have high intrapersonal intelligence, learning outcome of Chemistry course of the students who were given internet-based instructional media is higher than those who were given module-based instructional media, and (4) there is no significant difference of learning outcome of Chemistry course of students with low intrapersonal intelligence between those who were given internet-based instructional media and those who were given module-based instructional media